THE INFLUENCE OF ACADEMIC COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE KOTABUMI SUB-DISTRICT OFFICE, NORTH LAMPUNG REGENCY - Noviana, Linda; Z, Bustami (Saburai International Journal of Social Sciences and Development, 2024)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Performance improvement is the most important thing desired by both employees and the organization. To achieve these performance goals, it is necessary to increase academic competence and employee work discipline. From the results of interviews with 21 employees, it can be seen that indicators of low employee performance are still low, of course this is influenced by the condition of employees who are still lacking in discipline and the competence of employees who have high school education qualifications is still quite high. The type of research used is field research, which is quantitative in nature where the explanation is objective by explaining the existing approaches. This research will be carried out at the Kotabumi District Office, North Lampung Regency with a total sample of 21 respondents. The results of this study are (1) Academic Competency Variable (X1) influences employee performance (Y) by 58.7%. (2) Work Discipline Variable (X2) influences employee performance (Y) by 39.3%. and (3) Academic Competency Variables (X1) and Work Discipline (X2) simultaneously affect employee performance (Y) by 44.2%..